The Role of Local Government in Boosting Investment Under East Java Provincial Regulation No. 4 of 2021 - Udin Silalahi; Joy Zaman Felix Saragih; Sheila Ananda Siregar; Muhammad Daffa Syahputra; Jocelyn Phebelia Susanto; Ananda Bima Al Wajdi Majid Pranoto (Transpublika Publisher, 2026)
Investment plays a crucial role in driving regional economic growth, creating jobs, and improving public welfare. As part of the governance structure, local governments are responsible for creating a conducive investment climate through supportive policies and regulations. East Java Provincial Regulation Number 4 of 2021 concerning Investment serves as the legal basis for managing and developing investment in East Java. This study aims to analyze the role of local governments in increasing investment based on the provisions of this regulation and identify challenges in its implementation. The method used in this research is a normative-juridical approach, examining laws and regulations, legal documents, and related literature. The study results indicate that local governments play a role in formulating investment policies, simplifying licensing processes, providing incentives, and fostering and supervising investment activities. However, implementation still faces obstacles such as complex bureaucracy, limited supporting infrastructure, and suboptimal inter-agency coordination. Therefore, efforts to strengthen policies, improve licensing services, and foster synergy between local governments and business actors are needed to achieve the goal of increasing investment effectively and sustainably.